SOFOSBUVIR: TREATMENT OF CHRONIC HEPATITIS C AND THE MAIN TRENDS IN PATENT PROTECTION - V., LITVINOVA ELENA; V., POSILKINA OLGA; F., MASLOVA NATALIIA (International Journal of Applied Pharmaceutics, 2019)
The purpose of the study was to analyze and systematize the literature data on the benefit/risk ratio of sofosbuvir administration in the treatment of patients with chronic hepatitis C and the main trends in its patent protection. Studies were conducted using databases on the Internet: Ukrainian patent office, the European patent office, the US patent office, the Food and drug administration, European Medicines Agency (EMEA), State enterprise “The State Expert Center” of the Ministry of Health of Ukraine. It has used retrospective, logical, systematic and analytical methods. Data from clinical studies abroad and meta-analyses indicate that sofosbuvir is one of the most promising drugs for the treatment of chronic HCV infection. Its indisputable advantages are that this drug can be used with different genotypes of the virus, decompensated liver function, it is well tolerated. Sofosbuvir has an improved safety profile and a low probability of viral resistance. The high cost of sofosbuvir is due to the powerful patent protection. As mechanisms for working with patent barriers, it is recommended to use the flexible mechanisms of the TRIPS Agreement: the grant of compulsory licenses, the implementation of parallel imports, the tightening of the criteria for patentability (prohibition of patenting new forms that do not improve therapeutic efficacy).